Pengaruh Label Halal, Kesadaran Halal dan Bahan Makanan Terhadap Minat Beli Pempek 26 Ilir Kota Palembang Menurut Maqashid Syariah - Desmatuti, Mayang Fuji; Deskaryani, Yeyen; Panorama, Maya (Syntax Corporation, 2023)
Palembang City is the capital of South Sumatra Province which is not only famous as a city of culture and religion but also a city that is famous for its culinary. One of the culinary specialties of Palembang City, South Sumatra is pempek. The method used in this research is a quantitative method using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method approach and using the SmartPLS application. The results of this study indicate that food ingredients have an effect on Pempek Purchase Interest in Pempek Village 26 Ilir Palembang City. Meanwhile, halal label and halal Awareness has no effect in Purchase Intention of Pempek in Pempek Village 26 Ilir Palembang City.